Bringing PAI Learning to Life: The Role of Flipbook Maker in Increasing Student Motivation - Istianah, Ludfiatul; Wahono, Suparwoto Sapto; Mu'alimin, Mu'alimin (ATTA`DIB, 2025)
This study aims to analyze the impact of digital flipbook usage on students' learning motivation in Islamic Religious Education (PAI) at SDN 12 Sanur Denpasar. Based on initial observations, many students showed a lack of interest in PAI lessons due to conventional and less interactive teaching methods. The implementation of digital flipbooks was carried out through planning, execution, and evaluation stages. The findings indicate that digital flipbooks increased students' participation in learning, facilitated material comprehension, and provided opportunities for independent learning. Additionally, students' average scores improved from 70 to 85 after the implementation of this learning media. However, challenges such as limited technology access for some students and teachers' lack of skills in creating digital media were identified. Therefore, it is recommended to provide teacher training to enhance the effectiveness of digital learning media.